Sistem Keamanan Penghuni Apartemen Menggunakan Computer Vision Dan Raspberry Pi - Pritami Sergio; Zainul Munir (JURNAL QUANCOM: QUANTUM COMPUTER JURNAL, 2023)
This research aims to design and implement a security system for apartments that combines computer vision technology with notifications via the Telegram application. This system is based on the Raspberry Pi 3 Model B+ to detect the face of a person in front of the door via a connected camera, and sends notifications to residents via Telegram messages. Thus, this system effectively and automatically increases the level of security and provides residents with real-time access to information about the ongoing security situation in their apartments. This research explains the technical implementation of this system and its potential to increase the sense of security of apartment residents. Test results for familiar faces have an accuracy rate of 96% and for unfamiliar faces they have an accuracy rate of 96%.